Associations between brominated flame retardants in house dust and hormone levels in men - Johnson, Paula I. (2013)
Brominated flame retardants (BFRs) are used in the manufacture of a variety of materials and consumer products in order to meet fire safety standards. BFRs may persist in the environment and have been detected in wildlife, humans and indoor dust and air. Some BFRs have demonstrated endocrine and reproductive effects in animals, but human studies are limited. In this exploratory study, we measured serum hormone levels and flame retardant concentrations [31 polybrominated diphenyl ether (PBDE) congeners and 6 alternate flame retardants] in house dust from men recruited through a US infertility clinic. PBDE congeners in dust were grouped by commercial mixtures (i.e. penta-, octaand deca-BDE). In multivariable linear regression models adjusted by age and body mass index (BMI), significant positive associations were found between house dust concentrations of pentaBDEs and serum levels of free T4, total T3, estradiol, and sex hormone binding globulin (SHBG), along with an inverse association with follicle stimulating hormone (FSH). There were also positive associations of octaBDE concentrations with serum free T4, thyroid stimulating hormone (TSH), luteinizing hormone (LH) and testosterone and an inverse association of decaBDE concentrations with testosterone. Hexabromocyclododecane (HBCD) was associated with decreased SHBG and increased free androgen index. Dust concentrations of bis-tribromophenoxyethane (BTBPE) and tetrabromo-diethylhexylphthalate (TBPH) were positively associated with total T3. These findings are consistent with our previous report of associations between PBDEs (BDE 47, 99 and 100) in house dust and hormone levels in men, and further suggest that exposure to contaminants in indoor dust may be leading to endocrine disruption in men.